Interaction effect of primings and tobacco genotypes on some chemical constituents - Karim, Hevi Rahim; Mohammad, Mohammad Tofiq (Sulaimani Journal for Pure and Applied Sciences, 2020)
The study was conducted to estimate the percentage of reducing sugar, nicotine content, total nitrogen, total ash and volatile oil, potassium, chloride content and also C/N ratio in the leaves of different priming of oriental tobacco (Nicotiana tabacum L.). The study included leaves from three priming of five oriental tobacco genotypes, namely; Gullsur, Gullspi, Madara, Pazarjik, and Bulgari which were grown in Zrguz Tobacco Station in Sulaimani, during the summer season of 2010. The product was stored in the warehouse for a long time to induce natural fermentation and aging. The factorial experiment was laid out according to Completely Randomized Design, with three replicates. Tobacco leaves from lower, middle and upper primings were prepared to study the difference of genotypes, primings, and their combinations in some chemical constituents of leaves. Statistical analysis showed that there were highly significant differences among genotypes for all studied chemical constituents with the exception of total alkaloids as nicotine and chloride content. Also, the results indicated that there were highly significant differences between the primings regarding the studied chemical constituents except for the CN ratio and chloride content. The analysis also indicated that a combination between genotypes and primings were showed highly significant differences regarding all studied chemical constituents with the exception of total nitrogen and CN ratio, while the difference between the combination in chloride was significant.
Keywords: Oriental tobacco; Genotypes; Primings; chemical constituents